Strategi Pengurus Masjid Al-Mubarak dalam Memakmurkan Masjid Pasca Covid-19 - Nizham, M (Journal of Da'wah, 2024)
This research aims to find out the strategy of mosque administrators in making the Al-Mubarak Koto Dian, Telago and Limok Manaih mosques prosperous after Covid-19, to find out the management strategy of the Al-Mubarak Koto Dian, Telago and Limok Manaih mosques after Covid-19, to find out what are the supporting and inhibiting factors for the management and prosperity of the Koto Dian, Telago and Limok Manaih mosques after Covid-19, including worship, education, activities and maintenance. This research uses a qualitative research method by collecting data through observation, interviews and documentation. The approach used is a descriptive approach, in this case explaining the strategy of mosque administrators in making the Al-Mubarak Koto Dian, Telago and Limok Manaih mosques prosperous in post-Covid-1999. 19. Based on the results of research conducted on the strategy of the Al-Mubarak mosque management in making the mosque prosperous after Covid-19, it can be concluded that: (1) The management efforts of the Al-Muabarak Koto Dian, Telago and Limok Manaih mosque management are designing activities and maximizing them as well as organizing and managing the physical mosque. (2) Efforts by mosque administrators to make the Koto Dian Telago and Limok Manaih mosques prosperous by inviting the community to return to activities at the mosque after the pandemic with the aim of enlivening the mosque. (3) Supporting and inhibiting factors in the management of the Koto Dian, Telago and Limok Manaih mosques in making the mosque prosperous (post Covid-19) from supporting factors, very adequate facilities help mosque administrators to prosper the mosque. Meanwhile, the inhibiting factor is the pandemic itself